La inteligencia emocional y su incidencia en el desarrollo del autoestima de las niñas y niños de primer grado, del centro de educación general básica “Consejo Provincial” cantón Lago Agrio, provincia Sucumbíos. Período lectivo 2013-2014”. Lineamientos alternativos - Sucuchañay, María Rocío (2015)
This thesis refers to: "EMOTIONAL INTELLIGENCE AND ITS IMPACT ON THE DEVELOPMENT OF SELF-ESTEEM OF CHILDREN FIRST GRADE, THE BASIC GENERAL EDUCATION CENTER" PROVINCIAL COUNCIL "Lago Agrio Canton, SUCUMBÍOS province. LECTIVO PERIOD 2013-2014 " Alternative guidelines, the central research problem is How Emotional Intelligence influence on the development of self-esteem of the children from the first grade, the General Basic Education Center "Provincial Council" Canton Lago Agrio, Sucumbios Province. School period 2013-2014? It was proposed as general objective: Determine Emotional Intelligence and its impact on the Development of Self-esteem of children from First Degree, General Education Center Basic "Provincial Council" canton Lago Agrio, Sucumbios province. The methods used for the preparation of this research work were: scientific, inductive-deductive, analytic-synthetic and descriptive method and statistical model, the same that served effectively help to achieve the proposed goal. The techniques and instruments used were: a survey that was applied to the first grade teachers of General Basic Education Center "Provincial Council" Lago Agrio Canton to establish their activities to develop teachers and Emotional Intelligence Test Lewis Aiken esteem applied to children in first grade of General Basic Education Center "Provincial Council" Lago Agrio Canton, to assess the development of self esteem. It is concluded that: 100% of the surveyed teachers select activities for developing emotional intelligence as Identifies things that make you feel sad, appreciates the qualities of each; 67% is valued as a unique being, he discovers the consequences of what he says; and, 33% to name their feelings. With Self-Esteem Test Lewis Aiken, the results determine that: in the fourth step is equivalent to very satisfactory corresponds to 47%; the third step amounts to satisfactory corresponds to 33%; in the second step it is equivalent to unsatisfactory corresponds to 14%; and the first step is equivalent to unsatisfactory. To the managers of the Center for Basic Education to formulate projects to help children with problems of self-esteem, with the participation of professional psychologists, that after the analysis, understand their causes to provide timely and adequate care line to the needs of each child.